2005
DOI: 10.1080/10428190500083193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative animal models for the study of lymphohematopoietic tumors: strengths and limitations of present approaches

Abstract: The lymphomas probably represent the most complex and heterogenous set of malignancies known to cancer medicine. Underneath the single term lymphoma exist some of the fastest growing cancers known to science (i.e Burkitt's and lymphoblastic lymphoma), as well as some of the slowest growing (i.e. small lymphocytic lymphoma [SLL] and follicular lymphoma). It is this very biology that can dictate the selection of drugs and treatment approaches for managing these patients, strategies that can range from very aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The difficulty of DLBCL cells to engraft and disseminate after intravenous injection in immunodeficient mice has been described by other authors [16]. As a consequence of this difficulty, new drugs against DLBCL are generally tested in subcutaneous DLBCL xenografts [3] or in disseminated lymphoma models generated with intravenous injection of the aggressive Burkitt's lymphoma cells [5][6][7]. Genetically engineered mice (GEM) can also develop disseminated DLBCL [17][18][19] and they are very useful to evaluate the function of particular genes in tumour progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty of DLBCL cells to engraft and disseminate after intravenous injection in immunodeficient mice has been described by other authors [16]. As a consequence of this difficulty, new drugs against DLBCL are generally tested in subcutaneous DLBCL xenografts [3] or in disseminated lymphoma models generated with intravenous injection of the aggressive Burkitt's lymphoma cells [5][6][7]. Genetically engineered mice (GEM) can also develop disseminated DLBCL [17][18][19] and they are very useful to evaluate the function of particular genes in tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of patients with DLBCL present a widespread disease at diagnosis [2]. Most animal models that are used to test new drugs against DLBCL, however, still rely on subcutaneous xenografts [3], that mainly show only localized tumours. More disseminated xenograft lymphoma models are achieved after intravenous administration of the aggressive human Burkitt's lymphoma cells in SCID mice [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is thus an urgent need to develop novel, targeted therapies for this group of diseases, driven by advances in our understanding of their pathogenesis and specific prognosis. Current rodent models of lymphoma are far from predictive of the natural course of the human disease, relying either on the subcutaneous implantation of xenogeneic lymphoma cells into immune-compromised mice, or on genetic manipulations that artificially increase the likelihood of lymphoma in a monogenic fashion [4]. Key to advancing the field will be the development of natural, polygenic animal models of NHL, allowing the further interrogation of molecular and cellular pathogenesis, as well as trials of novel anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations are observed at the origin of the errors occurring during physiological events involved in the diversification repertoire of the germinal center, during class switch recombination (CSR) or somatic hypermutation (SHM) [28,29]. Experimental studies on animal models have confirmed the critical roll played by the induced activation of the cytidine deaminase enzyme in the physiology of CSR and SHM in the development of lymphoid tumors [30,31].…”
Section: Discussionmentioning
confidence: 91%